Aplicação de ferramentas de inteligência computacional para estimação das propriedades físicas de uma célula solar de silício - Matos, Fernando Barbosa (2011)
The development of computational models that can simulate the behavior of photovoltaic cells is of great importance in understanding this type of device. A new model is proposed to determine the types of dopants used in the manufacturing process, with the estimation of their concentrations. The use of techniques aided by computational intelligence based strategies allowed the creation of a new way to simulate and achieve results, regarding to the processing of mathematical model for photovoltaic cells. This new technique is not only able to get the types of dopants and their concentrations, but also minimize the amount of information required in term of number of variables needed to determine the behavioral characteristics of the solar cell under the parameters of voltage, current and power. The validity of the technique is treated in the theoretical and observed from the examples used during the tests applied software models PMCCF and PC-1D.